Mengidentifikasi Kendala Siswa Saat Berkomunikasi Dengan Teman Sebaya - Lesmana, Gusman; Laila, Laila; Anggraina, Yunissa Aristi (Universitas Labuhanbatu, 2024)
Peer association is an interaction with people who have the same age, status, hobbies and thoughts, in interacting they consider and prefer to join with people who have similarities in these things, so that it can influence ethics. communicate. This is generally the basis for the purpose of this analysis, namely to reveal and describe the big picture of peer interactions, how big is the picture of peer communication ethics.